Uma estrutura de suporte para adaptação em jogos 3D multiusuário - Silva, Alessandro Rodrigues e (2003)
With the growing dissemination and reliability of wireless networks and the emergence of devices with more and more processing and communication power, applications up to now restricted to PCs are being envisaged to run on devices as heterogeneous as wrist clocks with GPS locators, refrigerators with internet access, up to mobile phones, PDAs, settop- boxes and game consoles. The integration of this myriad of devices and network technologies, with different capabilities, demand special attention from the software programmers and designers specially when these applications are shared among multiple users from different devices, each one producing and consuming information according to each device capacity. In this sense, application adaptation, which allows a software to react upon the resources variations used, is an important process towards fitting the application to a certain device configuration. This adaptation is being considered as an important part of the systems that act upon heterogeneous processing and communication environment. Therefore, a large amount of work has been done in the traditional multimedia adaptation, such as text, images, audio and video, less attention has been focused on 3D digital content first because of the complexity involved in the 3D applications adaptation issues, and also because true marketing opportunities for 3D graphics in heterogeneous devices have just began to emerge. Moreover, initiatives that promote adaptation standardization must be considered, so that interoperability among adaptation mechanisms can become a reality. This work investigated the MPEG-4 standard and its extension MPEG-J to handle adaptation issues, and proposes an adaptation framework for 3D multi-user game applications, entitle MMGAME. With this framework, elements composing a game application can be adapted according to devices resources variations where the application is running as well as in the network where is connected.